Effect Of Yogic Exercise On Selected Physical Fitness Components Among High School Boys & Girls At Secondary Educational School In Hyderabad District (International Journal of Food and Nutritional Sciences, 2022)
Yoga, as it gains popularity from people of all walks of life, is also compared with many movement based practices, especially physical fitness exercises. The apparent similarity of external movements makes one sometimes to equate yoga with exercises. The purpose of the study is to find out the effect of Yogic Exercise on selected physical fitness components i.e speed, agility and endurance of boys and girls at Secondary Educational schools in Telangana state. Tools Used: Yogic Exercises – Padmasana – Siddhasana – Pachimottanasana – Bhujangasana – Dhanurasana – Kurmasana - Pranayama exercises Physical Fitness Components are Speed, Agility & Flexibility. The samples were collected from the 100 high school students (50 Boys & 50 Girls) in the age group of 12- 16 years from Govt. High School, Hyderabad. Finding of the study The Hyderabad district secondary boy’s students mean value of speed pre - test is 11.32, SD value is 4.659, and for post - test the Hyderabad district secondary boy’s students mean value is 08.22 and SD value is 4.421. The Hyderabad district secondary boy’s students mean value of agility pre - test is 13.26, SD value is 0.623, and for post - test the Hyderabad district secondary boy’s students mean value is 11.12 and SD value is 1.426. The Hyderabad district secondary boy’s students mean value of flexibility pre - test is 10.671, SD value is 1.347, and for post - test the Hyderabad district secondary boy’s students mean value is 12.32 and SD value is 2.252. The Hyderabad district secondary girl’s students mean value of speed pre - test is 11.122, SD value is 3.565, and for post - test the Hyderabad district secondary girls students mean value is 9.212 and SD value is 2.314. The Hyderabad district secondary girl’s students mean value of pre - test agility is 12.212, SD value is 2.432, and for post - test the Hyderabad district secondary girls students mean value is 11.122 and SD value is 1.426. The Hyderabad district secondary girl’s students mean value of flexibility pre - test is 10.886, SD value is 1.425, and for post - test the Hyderabad district secondary girls students mean value is 12.312 and SD value is 3.421. Conclusion: Hence, it is finally concluded that the Effect of Yogic Exercises on physical fitness have shown a positive impact among Pre-Test and Post-Test High school boys and girls in Govt. High School, Hyderabad district in relation to their physical fitness components i.e. speed, agility and flexibility. Physically fit people are able to withstand fatigue for longer periods and are better equipped to tolerate physical stress. Physical fitness is considered as one of the most valuable assets and it has received a high priority in all thoughts and actions. Keywords: Yogic Exercises, Physical Fitness, speed, agility & flexibility